Appendix 5.16: Confidential Cable from the US Embassy in Manila, “Marcos Delivers Major Economic Policy Speech with Minor Results,” 22 November 1976 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Part of Marcos’s mystique is his oratorical prowess, which seems to have more resonance among his (online) admirers than his writing skills. YouTube videos of him addressing audiences in straight English may partly account for that. However, this cable shows that Marcos was not always the electrifying speaker his loyalists project him to be. At one point, according to Ambassador William H. Sullivan, “[even] an obvious effort by cabinet members present to stimulate applause fell so flat, Marcos felt obliged to make a joke of it.” Moreover, this cable shows a growing perception that Marcos does not have particularly novel economic policies despite his Third Worldism/New Society rhetoric.